DEEP LEARNING PEDAGOGY IN SBDP INSTRUCTION FOR THE 6C SKILL IN ELEMENTARY SCHOOL - Shinta Marina; Heni Komalasari; Dedeh Komalasari (Universitas Majalengka, 2026)
Abstract Current curriculum developments in Indonesia require that SBDP instruction in elementary schools focus not only on artistic skills but also on 21st-century skills. The Merdeka Curriculum calls for the 6C competencies to be developed more meaningfully through an approach that enhances skills using Deep Learning Pedagogy. This study aims to analyze the role of Deep Learning Pedagogy in SBDP instruction for the development of the 6C competencies in elementary schools under the Merdeka Curriculum. The method used is a literature review, analyzing various relevant scientific articles, books, and conference proceedings, followed by a descriptive-qualitative analysis to identify relationships among the variables. The findings indicate that Deep Learning Pedagogy in SBDP instruction emphasizes active, reflective, contextual, and meaningful learning experiences. This approach provides students with opportunities to develop creativity, critical thinking, communication, collaboration, character, and integrated citizenship. SBDP learning designed through exploration, appreciation, creation, and reflection is proven to be relevant to the 6C competency dimensions as it encourages students to express ideas, solve problems, work together, and foster social and cultural awareness. This research contributes to a conceptual synthesis that affirms the relevance of Deep Learning Pedagogy in SBDP learning as a reference for developing the 6C competencies in elementary schools and as a guide for teachers and researchers in designing learning aligned with the Merdeka Curriculum. SBDP serves as a space for the development of transformative competencies in response to current learning challenges and the strengthening of the Pancasila Student Profile, which emphasizes adaptability, creativity, collaboration, and competitiveness. Keywords: Deep Learning Pedagogy; SBDP Learning; 6C Skills; Elementary School; Merdeka Curriculum